PENGARUH PROMOSI, KEPERCAYAAN, KEMUDAHAN TERHADAP KEPUTUSAN PEMBELIAN PADA PT. BILLINDO UTAMA - Lin, Kelly; Evyanto, Winda (SCIENTIA JOURNAL, 2023)
This study aims to examine and analyze the effect of promotion, trust, and convenience on purchasing decisions of PT. Billindo Utama. The variables in this study are promotion variables (X1), trust (X2), ease (X3) of purchasing decisions (Y) at PT. Billindo Utama. The number of samples in this study were 100 consumers. The sampling technique uses accidental sampling. Testing the effect in this study used multiple linear analysis and analysis of the coefficient of determination (R2), testing the hypothesis using the t test and f test using the SPSS version 25 software program. The results showed the influence of promotion, trust, and convenience variables. partially and simultaneously have a significant effect on purchasing decisions at PT Billindo Utama in Batam City.